2020
DOI: 10.3389/fchem.2020.00310
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Porphyrin Units by Random Copolymerization Into NDI-Based Acceptor for All Polymer Solar Cells

Abstract: Naphthalene diimide (NDI)-based polymer N2200 is a promising organic polymer acceptor for all-polymer solar cells (all-PSCs), but its inherent shortcomings like poor extinction coefficient and strong aggregation limit further performance optimization of all-PSCs. Here, a series of random copolymers, PNDI-Px, were designed and synthesized by introducing porphyrin unit into NDI-based polymer as acceptors for all-PSCs. These random copolymers show a higher absorption coefficient and raised the lowest unoccupied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Researchers have developed numerous acceptor materials based on NDI by adjusting the conjugated main chain, 52,53 flexible side chains 54,55 and ternary random copolymerization. [56][57][58] Kim et al 52 designed and synthesized two new polymer acceptors (PNDITCVT-HD and PNDITCVT-OD, Fig. 2e) by incorporating electron-withdrawing cyanovinylene groups into the backbone of N2200.…”
Section: Msde Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have developed numerous acceptor materials based on NDI by adjusting the conjugated main chain, 52,53 flexible side chains 54,55 and ternary random copolymerization. [56][57][58] Kim et al 52 designed and synthesized two new polymer acceptors (PNDITCVT-HD and PNDITCVT-OD, Fig. 2e) by incorporating electron-withdrawing cyanovinylene groups into the backbone of N2200.…”
Section: Msde Reviewmentioning
confidence: 99%
“…Researchers have developed numerous acceptor materials based on NDI by adjusting the conjugated main chain, 52,53 flexible side chains 54,55 and ternary random copolymerization. 56–58…”
Section: All-poscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, due to the structural adjustability, unique electronic and photophysical properties of porphyrins, porphyrins have broad application in various areas and good prospects ( Zhang et al, 2018 ; Chen et al, 2020 ; Asghar et al, 2021 ; Liu and Cheng, 2021 ). Particularly, the NLO performance of porphyrins could be improved by the flexible modification of peripheral substituents or the hybridization with other materials ( Zawadzka et al, 2013 ; Woller et al, 2016 ; Hu et al, 2018 ; Biswal et al, 2019 ; Samal et al, 2019 ; Liu J. L. et al, 2020 ; Liu Z. et al, 2020 ; Liu and Cheng, 2021 ; Ramasamy et al, 2022 ). However, previous research indicated the self-aggregate behavior of porphyrins could lead to the formation of large macro-scale and fractal structures, causing a negative impact in the development of NLO devices in practice ( Kalachyova et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Compared with small molecule materials, polymer materials have better intrinsic stability, higher mechanical stability and more suitable for printed fabrication, therefore, allpolymer solar cells (all-PSCs) consisting of p-type polymer donors and n-type polymer acceptors have attracted more and more attention and research from different research groups. [12][13][14][15][16] Thanks to the tremendous efforts, such as optimization of molecular weight, [17,18] random copolymerization, [19][20][21] and optimization of deposition techniques, [22,23] many high efficiency devices have been widely reported, and the optimal PCE of all-PSCs has been improved to more than 15 %. [24][25][26][27] Nevertheless, the photovoltaic performance of all-PSCs still lags behind that of the current state-of-theart PSCs based on non-fullerene fused-ring electron acceptors.…”
Section: Introductionmentioning
confidence: 99%